What makes Italian sme entrepreneurs successful? The leverage effect of relational competencies - Gerli, Fabrizio; Tognazzo, Alessandra; Giubitta, Paolo (Piccola Impresa / Small Business, 2012)
We analyze the role of emotional intelligence competencies and their impact on business outcomes in a sample of entrepreneurs of small and medium sized Italian firms. We focus on the measurement of competencies by using a variety of tools and identify those ones that distinguish superior performers (i.e. distinctive competencies). Using factor and regression analysis we identify three factors of distinctive competencies and show that the relational dimension primarily affects organizational results. In particular, competencies such as Efficiency orientation, Organizational awareness and Teamwork are related to a higher firm financial performance.